2006
DOI: 10.1038/sj.ijo.0803440
|View full text |Cite
|
Sign up to set email alerts
|

Meal suppression of circulating ghrelin is normalized in obese individuals following gastric bypass surgery

Abstract: Objective: It has been proposed that the success of maintained weight loss in morbidly obese subjects following Roux-en-Y gastric bypass (RYGBP) surgery depends on inappropriately low circulating concentrations of the appetite-stimulating peptide ghrelin, being unresponsive to food intake. In this study, this hypothesis was examined. Design: Cross-sectional study with repeated blood samples in 40 subjects after 14 h of prolonged overnight fasting followed by a standardized mixed meal (770 kcal). Subjects: Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…However, decreased appetite after LAGB could be caused by altered mealtime changes in ghrelin, as has been reported for RYGB [43]; this hypothesis warrants future study. Although PP has been shown to inhibit appetite and food intake [45], our findings do not support a role for PP in LAGB-induced weight loss, consistent with data from studies on other bariatric procedures [26,27].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, decreased appetite after LAGB could be caused by altered mealtime changes in ghrelin, as has been reported for RYGB [43]; this hypothesis warrants future study. Although PP has been shown to inhibit appetite and food intake [45], our findings do not support a role for PP in LAGB-induced weight loss, consistent with data from studies on other bariatric procedures [26,27].…”
Section: Discussionmentioning
confidence: 87%
“…For the study population as a whole, the median age at the time of surgery was 46.6 (IQR 34.5-50.6) years, and the median BMI was 43 Table 1). The continued decrease in leptin levels between 6 and 12 months after surgery was not significant ( p=0.31).…”
Section: Characteristics Of the Study Population And %Ewl After Lagbmentioning
confidence: 99%
“…Schindler et al [8] showed an increase in fasting ghrelin accompanied by a paradoxical decrease in hunger 6 months after LAGB, thus suggesting that weight loss is independent of circulating ghrelin and relies on changes in eating behavior induced by gastric restriction. The decreased appetite after LAGB could be caused by altered mealtime changes in ghrelin, as has been reported for RYGB [44]. Since only fasting plasma samples were obtained, we did not examine whether LAGB affects mealtime changes in acylated ghrelin and insulin levels.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, plasma total ghrelin and obestatin levels were decreased after Roux-en-Y gastric bypass or microgastric bypass (Stenström et al, 2006) in rats. Most importantly, meal suppression of circulating total (Korner et al, 2006;Engström et al, 2007) and acyl (Korner et al, 2005(Korner et al, , 2006 ghrelin was normalized in obese persons after gastric bypass surgery. On the other hand, gastric banding surgery prevented the increase of plasma total ghrelin level after weight loss in obese Zucker rats, which supported the hypothesis that sustained weight loss observed after gastric banding did not depend solely on food restriction (Monteiro et al, 2007).…”
Section: Ghrelin Gene Products In Food Intake and Gut Motilitymentioning
confidence: 95%
“…Therefore, the assumption that systemic total ghrelin levels reflect acyl ghrelin secretion should be made with caution (Gauna et al, 2007). For instance, fasting plasma total ghrelin (Cummings et al, 2002a;English et al, 2002;Rigamonti et al, 2002;Shiiya et al, 2002;Erdmann et al, 2005;Korner et al, 2005Korner et al, , 2006le Roux et al, 2005b;Engström et al, 2007;Guo et al, 2007;Vicennati et al, 2007;Huda et al, 2009;), des-acyl ghrelin (Rodríguez et al, 2009), and obestatin (Guo et al, 2007;Nakahara et al, 2008) concentration were lower in obese than lean subjects, whereas acyl ghrelin concentration was higher in obese persons (Rodríguez et al, 2009). In addition, obese persons showed lower expression of GHS-R in omental adipose tissue (Rodríguez et al, 2009).…”
Section: A Obesitymentioning
confidence: 97%